Efficiency in endurance exercise: Efficiency of what? - Ettema, G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The debate on how to determine the efficiency of doing work in endurance sports and exercise is ancient but still ongoing. It is often argued that some of the energy consumed is not related to doing work and therefore the total energy consumption should be corrected for this, which is referred to as base-line subtraction. Often this is the metabolism at rest, but also metabolism when doing zero "external" work is used for this purpose. In delta efficiency the energy cost at some level of doing work is used as base-line. One problem with these subtractions regards the consistency of this baseline metabolism during exercise (Cavanagh and Kram, 1985). A more important one is if the paradigm is correct at all (Cavanagh and Kram, 1985; Ettema and Lorås, 2009). This issue is directly linked to the definition of the energy transforming system, i.e., the whole body (no base-line subtraction, gross efficiency) or the working muscles (which muscles base-line subtraction, but which one?). The ongoing discussion on the estimation and role of "internal" work (energy used to move body segments) is exemplifying. We argue that estimation of internal work cost i.e. making movements without external resistance (e.g. cycling at 0 Watts) is flawed and that total internal work in cyclic movements is zero. Energy that is linked to motion of body segments may be utilised for propulsion, but obviously this is impossible when one is not allowed to propel (zero external load). Even more, the term "internal" is misleading; once the energy transforming system is well defined, the only form of work of interest is "external" and therefore does not need this specification. We propose to regard the entire relationship between metabolic - and work rate, and consider efficiency an incomplete description of the relationship (thereby only providing partial understanding). The use of efficiency as a comprehensive variable for relative energy cost of doing work should be abandoned. We studied this relationship for cross-country skiing and cycling. Crosscountry skiing, irrespective of technique, requires considerably more energy than cycling for all work rates investigated. This difference is not explained by weight-bearing. The small but significant relationship between performance level and energy cost in ski-skating is most likely explained by perfection of technique (Sandbakk et al 2010). On the other hand, in bicycling the differences between groups (from top athlete to patients) is extremely small (if existing at all), indicating the low number of degrees of freedom in movement execution. This makes cycling and excellent exercise model for investigation of physiological aspects of energy conversion.